1990
DOI: 10.1093/carcin/11.2.219
|View full text |Cite
|
Sign up to set email alerts
|

The effects of X-irradiation, N-ethyl-N-nitrosourea or combined treatment on O6-alkylguanine-DNA alkyltransferase activity in fetal rat brain and liver and the induction of CNS tumours

Abstract: Wistar rats were treated in utero on day 16 of gestation either by X-irradiation (1 and 2 Gy), N-ethyl-N-nitrosourea (ENU, 50 mg/kg), or both in combination. The O6-alkylguanine-DNA alkyltransferase (AT) activity of the fetal brain and liver was analyzed and long-term observations were made to reveal any relationship between the O6-ethylguanine repair capability and tumour incidence in the organs of the offspring. The AT activity in the brain was affected to the same extent in the fetuses as in the dams. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The present risk assessment of combined exposure is consistent with a simple additive effect of the two carcinogens, but previously reported animal experiments showed that combined exposure could have either synergistic or antagonistic effects on cancer development [3,10,11,[17][18][19]. In our current study, we found both dose-dependent synergistic and antagonistic effects of X-ray/ENU exposure, suggesting the importance of the ENU and radiation doses for risk assessment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present risk assessment of combined exposure is consistent with a simple additive effect of the two carcinogens, but previously reported animal experiments showed that combined exposure could have either synergistic or antagonistic effects on cancer development [3,10,11,[17][18][19]. In our current study, we found both dose-dependent synergistic and antagonistic effects of X-ray/ENU exposure, suggesting the importance of the ENU and radiation doses for risk assessment.…”
Section: Discussionsupporting
confidence: 88%
“…For example, a synergistic effect of these agents was reported in mouse T-cell lymphomas [10,11], mouse liver and ovary tumors [12], rat hepatocyte foci [13], and rat intestinal tumors [14]; while an antagonistic effect, also known as an adaptive response or a hormetic effect [15,16], was found for rat central nervous system [17,18] and brain tumors [19]. Thus, the nature of interaction between combined treatments varies between experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly this effect requires substantiation with a large number of patients receiving only TBI. It is interesting to note that in rodents, ATase activity in a number of tissues was increased by a single dose of ionising radiation (Margison et al, 1985;Stammberger et al, 1990). Changes in the specific activity of peripheral lymphocyte…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, incidence of brain tumors, which were induced by ENU treated in utero, decreased after combined treatment with pre-exposed X-rays (1 and 2 Gy), showing antagonistic eŠect. The reduction of tumor incidence corresponded with the inductive eŠect of X-irradiation on O 6 -alkylguanine-DNA alkyltransferase (ATase), suggesting a protective role of IR by inducing ATase for subsequent ENU treatment (20). Induction of ATase by IR has been frequently observed in several tissues in vivo.…”
Section: Combined Ešect Of Ir and Alkylating Agentsmentioning
confidence: 95%
“…Non-genotoxic chemicals may aŠect cell proliferation, diŠerentiation and senescence. The experimental data on combined exposures are mostly accumulated for alkylating agents such as N-methyl-N-nitrosourea (MNU), N-ethyl-N-nitrosourea (ENU), 1,2-dimethylhidrazine (DMH), diethylnitrosamine (DEN) etc (15)(16)(17)(18)(19)(20)(21)(22).…”
Section: The Risk Factors That Interact With Radiation In Cancer Indu...mentioning
confidence: 99%